2017
DOI: 10.1002/cctc.201601501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extraction Methods on Structure and Valorization of Corn Stover Lignin by a Pd/C Catalyst

Abstract: With the significant development of efficient pretreatments of lignocellulosic biomass towards using carbohydrate compositions for biofuel production, the valorization of associated lignin products into valuable chemicals has gained much attention. Four lignins obtained by pretreatment of corn stover with emerging ionic liquid‐based mixed organic electrolytes (ILOE) and alkaline twin‐screw extrusion (ATSE) pretreatment technologies were characterized by gel permeation chromatography (GPC), FTIR, HSQC, 31P NMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 67 publications
(74 reference statements)
1
21
1
Order By: Relevance
“…By the comparison of spectra, the signal at about 20-30 ppm showed a significant intensity increase, which was ascribed to carbon atoms of aliphatic chains. The 31 P NMR spectroscopy proved to be a useful tool to study the structures of lignin [33]. Naturally, the different types of active OH groups (aromatic, aliphatic, and carboxylic) and the S/G/H ratio in lignin were evaluated to further investigate the structure of lignin.…”
Section: The Structure and Morphology Of Lignin And Its Biocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…By the comparison of spectra, the signal at about 20-30 ppm showed a significant intensity increase, which was ascribed to carbon atoms of aliphatic chains. The 31 P NMR spectroscopy proved to be a useful tool to study the structures of lignin [33]. Naturally, the different types of active OH groups (aromatic, aliphatic, and carboxylic) and the S/G/H ratio in lignin were evaluated to further investigate the structure of lignin.…”
Section: The Structure and Morphology Of Lignin And Its Biocompositesmentioning
confidence: 99%
“…Naturally, the different types of active OH groups (aromatic, aliphatic, and carboxylic) and the S/G/H ratio in lignin were evaluated to further investigate the structure of lignin. The spectra shown in Figure 4 presented resonances assigned to various units bearing free OH groups: Aliphatic OH groups (broad signal at 145-150 ppm), phenolic OH groups (at 141.5-144 ppm for S, at 139-140 ppm for G, and at 137-138.5 ppm for H), and carboxylic acid groups (at 136.2-134.5 ppm) [33]. Obviously, it was observed that the signals of S, G, H, and carboxylic acid groups in acetoacetate lignin decreased compared with initial lignin, expressing that most OH groups were consumed by chemical modification.…”
Section: The Structure and Morphology Of Lignin And Its Biocompositesmentioning
confidence: 99%
“…4 Thus, the behavior of the extracted lignin is substantially different, affecting the distribution of aromatic chemicals obtained from lignin. 54 The high ratio of condensed structures and short side chains in residue lignin will give rise to barriers to lignin depolymerization. 55 Current and emerging isolation methods need to be discussed concerning the characteristics of the extracted lignin as far as its potential for further biorefinery.…”
Section: Chemical Structure Of Ligninmentioning
confidence: 99%
“…Four lignins (ionic liquid-based mixed organic electrolytes extracted/enzymatic hydrolytic lignins (ILOE-EL/ILOE-EHL) and alkaline twin-screw extrusion extracted/enzymatic hydrolytic lignins (ATSE-EL/ATSE-EHL)) were depolymerized on Pd/C catalyst. 54 The extracted lignin presents much great activity for hydrogenolysis. After 2h reaction at 235 o C in methanol, the overall bio-oil yields of 61.7 and 57.9 wt% could be obtained from ATSE-EL and ILOE-EL,…”
Section: Monometallic Catalystmentioning
confidence: 99%
“…The 2D‐HSQC NMR determinations for all prepared lignin samples were carried out in a Bruker AVIII 400 MHz spectrometer. The 2D‐HSQC NMR determination was carried out according to a recently reported method ,. The spectral widths for the 2D‐HSQC NMR were 20000 Hz and 5000 Hz, respectively.…”
Section: Methodsmentioning
confidence: 99%